Mapping Research Trends on Mental Health Literacy Among University Students: A Bibliometric Systematic Review - Laksana, Eko Pramudya; Muslihati, Muslihati; Setiyowati, Arbin Janu; Nisa, Salsabila Kholifahtun; Hudha, Muhammad Nur; Soetan, Margaret Kehinde (Jurnal Kajian Bimbingan dan Konseling, 2025)
Mental health is a global issue that has received increasing attention, particularly among university students. Mental health literacy (MHL) is an important factor in promoting students' psychological well-being through knowledge, attitudes, and the ability to recognize and address mental health problems. This study aims to map the developmental trends of MHL research among university students in order to provide a comprehensive overview of the direction and focus of studies in this field. This research employed a bibliometric literature review approach by analyzing 48 journal articles indexed in the Scopus database and published between 2021 and 2025. The findings indicate that publications on MHL research have increased significantly from year to year, reflecting growing academic attention to student mental health issues. However, the mapping of disciplinary fields shows that research remains dominated by medical, psychological, and public health approaches, with a focus on depression, anxiety, stigma, and professional help-seeking. In contrast, educational approaches, including the integration of MHL into curricula, learning strategies, and pedagogical innovations, remain highly limited. This imbalance indicates a conceptual gap in the development of MHL literature in higher education. The findings provide a comprehensive overview of the current development of MHL research and may serve as a reference for researchers in identifying future research gaps. This study emphasizes the need to strengthen MHL research through educational approaches that are integrated into higher education systems in order to support sustainable efforts to improve university students' mental health.